Intrarenal Complement System Transcripts in Chronic Antibody-Mediated Rejection and Recurrent IgA Nephropathy in Kidney Transplantation - Cernoch, Marek; Hruba, Petra; Kollar, Marek; Mrazova, Petra; Stranavova, Lucia; Lodererova, Alena; Honsova, Eva; Viklicky, Ondrej (Frontiers in Immunology, 2018)
Background: The complement system activation and regulation have been linked to post-transplant pathologies including chronic antibody mediated rejection (cAMR) and the recurrence of IgA nephropathy (ReIgAN) but distinct mechanisms remain to be elucidated. Methods: In this retrospective single center study, the outcome of kidney transplantation was studied in 150 patients with late histological diagnosis to be either cAMR or ReIgAN, 14 stable kidney grafts at 3 months and finally 11 patients with native kidney IgAN nephropathy. To study a role of complement cascade and regulation in cAMR and ReIgAN, the RNA was extracted from available frozen kidney biopsy samples and using RT-qPCR transcripts of 11 target genes along with clinical data were determined and compared with stable grafts at 3 months protocol biopsies or IgAN native kidney nephropathy. Immunohistologically, CD46 (MCP), and C5 proteins were stained in biopsies. Results: Interestingly, there were no differences in kidney graft survival between cAMR and ReIgAN since transplantation. cAMR was associated with significantly higher intragraft transcripts of C3, CD59, and C1-INH as compared to ReIgAN (p < 0.05). When compared to normal stable grafts, cAMR grafts exhibited higher C3, CD55, CD59, CFH, CFI, and C1-INH (p < 0.01). Moreover, ReIgAN was associated with the increase of CD46, CD55, CD59 (p < 0.01), and CFI (p < 0.05) transcripts compared with native kidney IgAN. Rapid progression of cAMR (failure at 2 years after biopsy) was observed in patients with lower intrarenal CD55 expression (AUC 0.77, 78.6% sensitivity, and 72.7 specificity). There was highly significant association of several complement intrarenal transcripts and the degree of CKD regardless the diagnosis; C3, CD55, CFH, CFI, and C1-INH expressions positively correlated with eGFR (for all p < 0.001). Neither the low mRNA transcripts nor the high mRNA transcripts biopsies were associated with distinct trend in MCP or C5 proteins staining. Conclusions: The intrarenal complement system transcripts are upregulated in progressively deteriorated kidney allografts.